Downregulation of miR‐326 and its host gene β‐arrestin1 induces pro‐survival activity of E2F1 and promotes medulloblastoma growth. Issue 2 (31st December 2020) - Miele, Evelina; Po, Agnese; Mastronuzzi, Angela; Carai, Andrea; Besharat, Zein Mersini; Pediconi, Natalia; Abballe, Luana; Catanzaro, Giuseppina; Sabato, Claudia; De Smaele, Enrico; Canettieri, Gianluca; Di Marcotullio, Lucia; et al.
Abstract : Persistent mortality rates of medulloblastoma (MB) and severe side effects of the current therapies require the definition of the molecular mechanisms that contribute to tumor progression. Using cultured MB cancer stem cells and xenograft tumors generated in mice, we show that low expression of miR‐326 and its host gene β‐arrestin1 (ARRB1) promotes tumor growth enhancing the E2F1 pro‐survival function. Our models revealed that miR‐326 and ARRB1 are controlled by a bivalent domain, since the H3K27me3 repressive mark is found at their regulatory region together with the activation‐associated H3K4me3 mark. High levels of EZH2, a feature of MB, are responsible for the presence of H3K27me3. Ectopic expression of miR‐326 and ARRB1 provides hints into how their low levels regulate E2F1 activity. MiR‐326 targets E2F1 mRNA, thereby reducing its protein levels; ARRB1, triggering E2F1 acetylation, reverses its function into pro‐apoptotic activity. Similar to miR‐326 and ARRB1 overexpression, we also show that EZH2 inhibition restores miR‐326/ARRB1 expression, limiting E2F1 pro‐proliferative activity. Our results reveal a new regulatory molecular axis critical for MB progression. Abstract : Medulloblastoma (MB) is a malignant pediatric brain tumor, and we reveal a new regulatory molecular axis critical for MB progression. Low expression of miR‐326 and its host gene β‐arrestin1 (ARRB1) promotes tumor growth enhancing the E2F1 pro‐survival function. High levels of EZH2 are responsible for the presence of H3K27me3 that controls miR‐326 and ARRB1 through a bivalent domain. Restoration of miR‐326 and re‐expression of ARRB1 reverse E2F1 function into pro‐apoptotic activity.